RETRACTED: The Dynamics of Three Currencies’ Bid–Ask Spread From the Perspective of Import–Export Success: Novel Findings for Digital Trade and Sustainable Production - Xu, Lu; Liu, Xijing; Smutka, Luboš; Strielkowski, Wadim; Zhao, Xin (Frontiers in Environmental Science, 2022)
Import and export have been acknowledged for its beneficial effects on sustainable economic development. In the context of economic globalization, the dynamics of exchange rate is more critical and necessary to export success and sustainable development. Therefore, understanding dynamics of exchange rate contributes to the achievement of export success so as to promote sustainable production. This research aims to find out the dynamics of spreads in foreign exchange rates over 15 years and the systematic relationship between dynamics of spreads in foreign exchange rates and information arrival, dynamics of spreads and cost of carry. The Multiple Regression, the Dummy Variable Test and the Vector Autoregressive Model show that most variations in the spreads result from relative spread rather than information arrival and cost of carry for the long term. The information arrival and cost of carry have almost no influence upon relative spread, even during the global financial crisis in 2008.